Transcriptional Control of Gene Expression and the Heterogeneous Cellular Identity of Erythroblastic Island Macrophages - Mukherjee, Kaustav; Bieker, James J. (Frontiers in Genetics, 2021)
During definitive erythropoiesis, maturation of erythroid progenitors into enucleated reticulocytes requires the erythroblastic island niche comprising a central macrophage attached to differentiating erythroid progenitors. Normally, the macrophage provides a nurturing environment for maturation of erythroid cells. Its critical physiologic importance entails aiding in recovery from anemic insults, such as systemic stress or acquired disease. Considerable interest in characterizing the central macrophage of the island niche led to the identification of putative cell surface markers enriched in island macrophages, enabling isolation and characterization. Recent studies focus on bulk and single cell transcriptomics of the island macrophage during adult steady-state erythropoiesis and embryonic erythropoiesis. They reveal that the island macrophage is a distinct cell type but with widespread cellular heterogeneity, likely suggesting distinct developmental origins and biological function. These studies have also uncovered transcriptional programs that drive gene expression in the island macrophage. Strikingly, the master erythroid regulator EKLF/Klf1 seems to also play a major role in specifying gene expression in island macrophages, including a putative EKLF/Klf1-dependent transcription circuit. Our present review and analysis of single cell genetic patterns suggest novel expression characteristics that will enable a clear enrichment of EBI subtypes and resolution of island macrophage heterogeneity. Specifically, the discovery of markers such as Epor, and specific features for EKLF/Klf1-expressing island macrophages such as Sptb and Add2, or for SpiC-expressing island macrophage such as Timd4, or for Maf/Nr1h3-expressing island macrophage such as Vcam1, opens exciting possibilities for further characterization of these unique macrophage cell types in the context of their critical developmental function.